A case report of a patient involved in an alleged homicide–attempted suicide case - a theoretical discussion on the theory of homicide-suicide - Md Rosli, Ahmad Nabil; S, Suarn (2015)
This case report stresses the role of depression in the manifestation of a homicide attempted suicide. We report the case of a man who allegedly murdered his partner and then attempted suicide. Previously, he had several failures and rejections in relationships in addition to work-related stress. He was diagnosed with major depressive disorder and treated with antidepressant. The scarcity of homicide attempted suicide as exemplified in this case could give an insight to the Psychiatrist for better understanding and possible prevention.